2018
DOI: 10.1039/c8tc00568k
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized phenylimidazole-based facial-homoleptic iridium(iii) complexes and their excellent performance in blue phosphorescent organic light-emitting diodes

Abstract: Novel phenylimidazole-based blue-emitting iridium complexes were prepared and they showed the excellent electroluminescent performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…[31][32][33] The dissociation of the ancillary picolinate ligand and the cleavage of C-F bonds [34][35][36][37][38] were proposed to be responsible for its deactivation. Consequently, uorine-free homoleptic blue Ir( ) complexes [39][40][41][42] were prepared, and the ancillary ligand was changed to carbene [43][44][45] or pyrimidine [46][47] functionalities. Ligands were decorated with cyano groups 40 and pyrimidine moieties were introduced.…”
Section: Read Full License Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] The dissociation of the ancillary picolinate ligand and the cleavage of C-F bonds [34][35][36][37][38] were proposed to be responsible for its deactivation. Consequently, uorine-free homoleptic blue Ir( ) complexes [39][40][41][42] were prepared, and the ancillary ligand was changed to carbene [43][44][45] or pyrimidine [46][47] functionalities. Ligands were decorated with cyano groups 40 and pyrimidine moieties were introduced.…”
Section: Read Full License Introductionmentioning
confidence: 99%
“…Consequently, uorine-free homoleptic blue Ir( ) complexes [39][40][41][42] were prepared, and the ancillary ligand was changed to carbene [43][44][45] or pyrimidine [46][47] functionalities. Ligands were decorated with cyano groups 40 and pyrimidine moieties were introduced. Fluorine-free, homoleptic phenylimidazole-based Ir( ) dopants showed promising performance, 24,41 but the improvement in OLED device lifetimes were only moderate.…”
Section: Read Full License Introductionmentioning
confidence: 99%
“…These moieties have high radiative efficiency and excellent chemical stability. [ 18,19,22–25,34–48 ] Recently, Kido and co‐workers reported an external quantum efficiency (EQE) of over 30% using fluorine‐free, N ‐phenyl‐substituted, phenylimidazole‐based facial ‐Ir(mpim) 3 as a sky‐blue triplet emitter. [ 40 ] Our group has reported a cyanide‐substituted phenylimidazole ligand‐based facial ‐Ir complex demonstrating a high EQE (22.5%) with a Commission Internationale de l'Eclairage (CIE) y color space coordinate of 0.28 in OLED devices.…”
Section: Figurementioning
confidence: 99%
“…[ 34 ] Although the emission spectra demonstrated a second maximum at λ em = 485 nm (emissive band indicating vibrionic coupling) with a tail to ≈600 nm, the full width at half maximum (FWHM) of the emission at 456 nm in toluene was considerably narrow (56 nm, Table 1) compared to that (73–80 nm) for imidazole‐ligand‐based iridium complexes. [ 44 ] The significantly narrow FWHM proved that the emissive band was mainly attributable to locally excited transitions (e.g., ligand‐centered (LC) transitions, vide infra) and MLCT transitions. The slight shift of the emissive centers in TzIr owing to variations in the solvent polarities (Δλ em < 1 nm, measured in cyclohexane, tetrahydrofuran, and dichloromethane, Figure S4, Supporting Information) also indicated that such emissions resulted from locally excited transitions.…”
Section: Figurementioning
confidence: 99%
“…Iridium(III) complexes have been widely studied in applications 1,2 such as photocatalysis, 3 biological labelling, 4 sensing 5 and as emitters in highly efficient phosphorescent organic lightemissive devices (PhOLEDs) [6][7][8][9][10][11][12] They possess a range of advantageous properties such as high luminescence quantum efficiency (Φ), microsecond-scale phosphorescence lifetime (η) and good electrochemical stability, while their metal-ligand based photochemistry has enabled their emission colour to be tuned across the entire visible spectrum through appropriate synthetic modification. [13][14][15] Notably, highly phosphorescent heteroleptic complexes have received significant interest because they can be synthesized under milder conditions than fac-homoleptic complexes, allowing a wider scope for structural variation.…”
Section: Introductionmentioning
confidence: 99%